Desenvolvimento humano e sustentabilidade nas organizações sob a ótica dos profissionais de recursos humanos - Lima, Vanessa Oliveira (2017)
Subscribed to the theme of studies on human development and formation in organizations, this research aimed to answer the following question: what is the meaning of Human Development and Sustainable Development for Human Resources professionals and what educational actions are triggered in organizations from your conceptions? To answer this question, a study was conducted in seven large Brazilian organizations, whose selection criterion was the incorporation in their strategy and mission of objectives aimed at Human and Sustainable Development. From the methodological point of view, this research presents a qualitative approach, adopting in-depth interviews as the main data construction strategy, complemented by document analysis of the organizations under study. The results showed that HR professionals attribute a pragmatic meaning to the concept of DH and DS, connecting it strongly to organizational goals and issues related to daily work. They refer to the career plan, to professional performance, as a way to gain competitive advantage, in a clear distance from a broader perspective that considers Human Development and Sustainable Development as a human flowering. DH and DS were thematic contingencies in the agenda of human resources professionals surveyed, little integrated the strategies and educational architecture of the organizations object of this study, pointing to few advances in relation to the role that literature has attributed to human resources in this context. The pragmatism of educational, capacity building and development actions addressed to DH and DS does not give HR a role of change agent. Both the idea of human development and sustainable development are subjugated in the HR policies and practices of the companies studied. As a trend, they point to the continuity of traditional training initiatives, aimed at solving technical problems, complying with legislation and seeking socio-environmental certifications, away from a reflexive and critical process that DH and DS demand. Consequently, new skills are not necessarily being developed as a DH and DS HR training policy, indicating that changes are not underway in the short or long term. It is hoped that this study contributed to the reflection on the advancement of understanding about the meaning of Human Development and Sustainable Development in organizations, as well as the role that Human Resources professionals and their educational actions have assumed in this context.